2010
DOI: 10.1105/tpc.110.076760
|View full text |Cite
|
Sign up to set email alerts
|

Phosphoinositides Regulate Clathrin-Dependent Endocytosis at the Tip of Pollen Tubes inArabidopsisand Tobacco

Abstract: Using the tip-growing pollen tube of Arabidopsis thaliana and Nicotiana tabacum as a model to investigate endocytosis mechanisms, we show that phosphatidylinositol-4-phosphate 5-kinase 6 (PIP5K6) regulates clathrin-dependent endocytosis in pollen tubes. Green fluorescent protein-tagged PIP5K6 was preferentially localized to the subapical plasma membrane (PM) in pollen tubes where it apparently converts phosphatidylinositol 4-phosphate (PI4P) to phosphatidylinositol 4,5-bisphosphate [PI(4,5)P 2 ]. RNA interfere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
193
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(211 citation statements)
references
References 60 publications
(107 reference statements)
13
193
0
2
Order By: Relevance
“…In addition, exogenous PtdIns(4,5)P 2 stimulates the internalization process in WT cells ( Figure 5B), which strongly suggests that vesicle trafficking, especially endocytosis, is affected by PIP5K2 through its product PtdIns(4,5)P 2 . These results are similar to previous findings that disruption of PIP5K4 inhibits proper endocytosis and membrane recycling in pollen tubes [21] and consistent with the report that PIP5K6 and PtdIns(4,5)P 2 positively regulate clathrin-dependent endocytosis [18].…”
Section: Pip5k2/ptdins(45)p 2 Regulates Vesicle Trafficking and Is Csupporting
confidence: 82%
See 1 more Smart Citation
“…In addition, exogenous PtdIns(4,5)P 2 stimulates the internalization process in WT cells ( Figure 5B), which strongly suggests that vesicle trafficking, especially endocytosis, is affected by PIP5K2 through its product PtdIns(4,5)P 2 . These results are similar to previous findings that disruption of PIP5K4 inhibits proper endocytosis and membrane recycling in pollen tubes [21] and consistent with the report that PIP5K6 and PtdIns(4,5)P 2 positively regulate clathrin-dependent endocytosis [18].…”
Section: Pip5k2/ptdins(45)p 2 Regulates Vesicle Trafficking and Is Csupporting
confidence: 82%
“…Besides 4 homologs of yeast PIP5K, 11 PIPK isoforms can be divided into two subfamilies (A and B) according to their domain organization [14]. The catalytic activities of using PtdIns4P as the preferred substrate to generate PtdIns(4,5)P 2 have all been characterized [15][16][17][18]. Studies have revealed the physiological functions of some PIP5Ks, including PIP5K1 in abscisic acid signaling [19]; PIP5K3 in root hair formation and growth [16,20]; PIP5K4 in stomata opening [21]; and PIP5K4-6 in pollen tube growth [17,22].…”
Section: Introductionmentioning
confidence: 99%
“…2g), suggesting that it may play an essential role, possibly in filament elongation at anthesis Zhao et al, 2010). This would not be surprising given that two phosphatidylinositol compounds in the lipiddependent PA synthesis pathway, phosphatidylinositol 4,5-bisphosphate (PtdIns(4,5)P 2 ) and phosphatidylinositol 3,4,5-trisphosphate (PtdIns(3,4,5)P 3 ), participate in the recruitment and activation of a wide variety of actin regulatory proteins at the plasma membrane, controlling cell shape, motility, and cytokinesis (di Paolo and de Camilli, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, actin dynamics have been implicated in mediating Ca 2+ concentration changes in the cytosol, K + channel activity, and vacuole shape determination (Hwang et al, 1997;Gao et al, 2009;Zhao et al, 2013), but the related molecular mechanisms remain to be established. One possibility is regulation of membrane recycling by actin reorganization Lee et al, 2008;Zhao et al, 2010;Bou Daher and Geitmann, 2011;Zhu et al, 2013), which would change the localization of ion channels/transporters and the area of vacuolar membrane. Actin dynamics may also act as an important component in signal transduction to mediate such changes (Gao et al, 2008;Zhao et al, 2011Zhao et al, , 2013Jiang et al, 2012).…”
Section: Discussionmentioning
confidence: 99%